The Urgency of Sports Health Law Tools in the New Normal Era - Wandik, Yos; Qomarrullah, Rif’iy; Sawir, Lestari Wulandari; Muhlisin, Muhlisin; Sugiharto, Sugiharto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
Corona Virus Disease 2019 or Covid-19 has been declared a pandemic determined by the World Health Organization (WHO). In addition to causing health emergencies, the presence of this virus also has implications for several sectors, such as finance, which originates from an unstable economy. Based on this, the role of the state is needed to ensure prevention and handling. Indonesia as a rule of law country actually has to guarantee certainty and protection of its citizens through the handling set forth in a regulation and the establishment of a synergy between the center and the regions. Then, preventive steps through this literature research review will comprehensively examine the state of the Covid-19 pandemic in Indonesia and regarding the urgency of sports health law tools in the new normal era in handling this pandemic both at the central and regional levels even through handling in perspective. emergency constitutional law. This research uses normative juridical research by means of a statutory approach and is obtained through literature study as a reference source. The results of this study are to explain and explain the role and efforts of the state in handling the pandemic as a manifestation of the purpose of the presence of the state, namely protecting the entire Indonesian nation through health sports in the new normal era.